Advanced oxidation processes for in-situ production of hydrogen peroxide/hydroxyl radical for textile wastewater treatment: A review - Asghar, A.; Abdul Raman, Abdul Aziz; Daud, Wan Mohd Ashri Wan (Elsevier, 2015)
Fenton Process, a type of Advanced Oxidation Processes is an efficient method for treating textile wastewaters. However, excessive use of hydrogen peroxide and catalyst has made this process economically non-feasible. Besides, industrial grade hydrogen peroxide costs 390-500 per ton. One of the means to overcome this problem is the in-situ production of hydrogen peroxide. In this paper, a detailed review was conducted on the generation methods, degradation potential and optimum operating parameters for in-situ production of hydrogen peroxide/hydroxyl radicals. Additionally the scavenging aspect for hydroxyl radicals was also investigated. From this review, it can be concluded that hydroxyl radical is highly oxidative and non selective in nature and its in-situ production can be performed through application of catalyst, ozonation, photocatalysis, electro and microbial fuel cells. Furthermore, optimization of operating parameters can result in an increase in the yield of hydroxyl radicals/hydrogen peroxide. Sonolysis as an auxiliary tool has potential to induce synergetic effects in combination with Advanced Oxidation Processes to increase in-situ hydrogen peroxide production. However, the problem of the scavenging effect is an aspect that needs to be dealt with, as hydroxyl radicals are prone to deactivation by scavengers. Therefore based on the review, it is concluded that insitu production of hydrogen peroxide/hydroxyl radical for treating textile wastewater is economically viable and practically feasible if careful selection of process is conducted through selective research. (C) 2014 Elsevier Ltd. All rights reserved.